Analysis of grinding mechanics and improved predictive force model based on material-removal and plastic-stacking mechanisms. (November 2017) - Zhang, Yanbin; Li, Changhe; Ji, Heju; Yang, Xiaohui; Yang, Min; Jia, Dongzhou; Zhang, Xianpeng; Li, Runze; Wang, Jun
Abstract: Numerous researchers have developed theoretical and experimental approaches to force prediction in surface grinding under dry conditions. Nevertheless, the combined effect of material removal and plastic stacking on grinding force model has not been investigated. In addition, predominant lubricating conditions, such as flood, minimum quantity lubrication, and nanofluid minimum quantity lubrication, have not been considered in existing force models. This work presents an improved theoretical force model that considers material-removal and plastic-stacking mechanisms. Grain states, including cutting and ploughing, are determined by cutting efficiency ( β ). The influence of lubricating conditions is also considered in the proposed force model. Simulation is performed to obtain the cutting depth ( a g ) of each "dynamic active grain." Parameter β is introduced to represent the plastic-stacking rate and determine the force algorithms of each grain. The aggregate force is derived through the synthesis of each single-grain force. Finally, pilot experiments are conducted to test the theoretical model. Findings show that the model's predictions are consistent with the experimental results, with average errors of 4.19% and 4.31% for the normal and tangential force components, respectively. Highlights: Grinding force model based on material removal and plastic stacking mechanism is built. Dynamic active grains in grinding zone are classified into cutting and ploughing grains. β presents a S-shaped trend with the increase of a g, a g  = 1.18 μm was the critical value. Tribological tests is conducted to obtain μ under different lubricating conditions. Model shows 4.19% and 4.31% of the average error for the normal/tangential force.